Cyanobacteria in microbialites of Alchichica Crater Lake: a polyphasic characterization. Issue 4 (2nd October 2021) - Águila, Bernardo; Alcántara-Hernández, Rocío J.; Montejano, Gustavo; López-Martínez, Rafael; Falcón, Luisa I.; Becerra-Absalón, Itzel
ABSTRACT: We analysed and characterized the cyanobacteria in microbialites of Alchichica crater lake over a depth gradient, from 3 to 30 m. A polyphasic approach was followed using morphometry, optical and epifluorescence microscopy, and molecular methods. Regions V3–V4 of the 16S rRNA conserved for cyanobacteria were amplified and used for clone library construction. Independently, a NGS library was constructed using the V4 region of the 16S rRNA. To complement the analysis, eight monocultures of cyanobacteria were isolated from microbialites, which were also characterized by microscopy and 16S rRNA sequencing. In total, we described 18 genera of cyanobacteria isolated from microbialites of Alchichica crater lake. The distribution pattern suggests that on the surface there were mostly Nostocales and filamentous Synechococcales, while at depth we found single-celled Synechococcales. Pleurocapsales and Chroococcales were found at all depths, increasing in abundance at 20 and 30 m.